2019
DOI: 10.1177/1744806919832718
|View full text |Cite
|
Sign up to set email alerts
|

Calcitonin gene-related peptide potentiated the excitatory transmission and network propagation in the anterior cingulate cortex of adult mice

Abstract: The neuropeptide of calcitonin gene-related peptide (CGRP) plays critical roles in chronic pain, especially in migraine. Immunohistochemistry and in situ hybridization studies have shown that CGRP and its receptors are expressed in cortical areas including pain perception-related prefrontal anterior cingulate cortex. However, less information is available for the functional roles of CGRP in cortical regions such as the anterior cingulate cortex (ACC). Recent studies have consistently demonstrated that long-ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 39 publications
6
40
0
Order By: Relevance
“…Previous studies of central synaptic transmission influenced by CGRP are mainly focused on the PBN, amygdala, the bed nucleus of the stria terminalis and spinal cords [17,34,35]. In the present study, we demonstrate that CGRP enhanced the synaptic transmission in the IC, which is like our recent study in the ACC [21]. We found that CGRP induced potentiation is NMDAR independent for the role of CGRP in the IC.…”
Section: Modulation Of Synaptic Transmission By Cgrp In the Icsupporting
confidence: 88%
“…Previous studies of central synaptic transmission influenced by CGRP are mainly focused on the PBN, amygdala, the bed nucleus of the stria terminalis and spinal cords [17,34,35]. In the present study, we demonstrate that CGRP enhanced the synaptic transmission in the IC, which is like our recent study in the ACC [21]. We found that CGRP induced potentiation is NMDAR independent for the role of CGRP in the IC.…”
Section: Modulation Of Synaptic Transmission By Cgrp In the Icsupporting
confidence: 88%
“…Our recent study showed that CGRP increased the excitatory synaptic transmission in the ACC [21]. Here we wanted to see if similar effect would be found in the IC, which also plays important roles in pain perception and chronic pain.…”
Section: Cgrp Enhanced Excitatory Synaptic Transmission In the Icmentioning
confidence: 79%
“…Cumulative evidences suggest that CGRP-containing pathways could convey nociceptive and visceral sensation from the posterior thalamus and parabrachial nuclear (PBN) complex to the IC and the amygdala [2]. Immunohistochemistry and in situ hybridization researches have also shown that CGRP and its receptors are expressed in some cortical areas, including the IC and anterior cingulate cortex (ACC) [21,22]. Our previous study indicates that CGRP may contribute to synaptic potentiation in the ACC [21].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…MED64 planar microelectrode array recording system was purchased from Alpha Med Science, Japan and used for electrophysiological recordings (32). ACSF for recording use was prepared containing 120 mM NaCl, 27 mM NaHCO 3 , 20 mM glucose, 1 mM NaH 2 PO 4 , 3 mM KCl, 2.6 mM CaCl 2 and 1 mM MgCl 2 .…”
Section: Electrophysiologymentioning
confidence: 99%